5 - La protection des réfugiés en Afrique: pour une réforme de l’asile au Sénégal. - Ndiaye, Ndeye Dieynaba (African Sociological Review, 2023)
After presenting a historical understanding of the notion of “asylum”, of its conditions in Africa and of its international transformations since World War II and the African Independences, this article offers, in its second part, an analysis of the protection of refugees and asylum seekers and its limits in Senegal. The analysis explores the various measures decided by the Senegalese authorities over the decades, with regard to the African refugee protection system and the international Refugee Law Council. Thus, this analysis aims at contributing towards a reform of local policies.